CORPORATE SOCIAL RESPONSIBILITY IN THE PHARMACEUTICAL INDUSTRY: A COMPARISON STUDY ON INDONESIAN AND AUSTRALIAN FIRMS - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
Corporate social responsibility (CSR) is essential for both the society and more so, specifically the pharmaceutical industry. Companies now measure success in multiple ways beyond just profits, such as benefits to society. This is the “triple bottom line” approach, it takes into account stakeholders in addition to shareholders. Businesses are now seeing the long-term value of giving back to the society in which they conduct business. Sustaining health in various communities can raise the standard of living, increasing paying customers and instilling brand loyalty. In addition, there is evidence that mitigating negative public perception can relieve some of the excessive regulation that is now in place. Within this context, I provide real-world examples of CSR programs that pharmaceutical companies are currently engaged in and show how these programs help both society and the pharmaceutical industry itself. In closing, I discuss opportunities for the pharmaceutical industry’s current CSR initiatives.